2005
DOI: 10.1200/jco.2005.01.6550
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Menopausal Symptoms, and Cognitive Function in Women After Adjuvant Chemotherapy for Breast Cancer: 1- and 2-Year Follow-Up of a Prospective Controlled Study

Abstract: Fatigue, menopausal symptoms, and cognitive dysfunction are important adverse effects of chemotherapy that improve in most patients. Hormonal treatment has minimal impact on them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
140
1
14

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(162 citation statements)
references
References 26 publications
3
140
1
14
Order By: Relevance
“…In cross-sectional studies that used test norms 1 or control groups consisting of healthy participants, 4,6,13 cognitive compromise in the patients may have originated before chemotherapy, like it did in the current study. However, several cross-sectional studies have used control groups consisting of patients with breast cancer who were treated without chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In cross-sectional studies that used test norms 1 or control groups consisting of healthy participants, 4,6,13 cognitive compromise in the patients may have originated before chemotherapy, like it did in the current study. However, several cross-sectional studies have used control groups consisting of patients with breast cancer who were treated without chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…11 Data regarding affected cognitive domains and the duration of cognitive disturbance are far from being congruent. 5,12,13 It remains unknown which cytostatic agents are responsible for cognitive impairment, which characteristics make patients vulnerable, 14 and which biologic mechanisms are involved. 15 Some doubts regarding the evidence for chemotherapy-induced cognitive impairment have been raised by 3 recently published studies that failed to confirm the adverse effects of chemotherapy on cognitive function.…”
mentioning
confidence: 99%
“…Because many patients become longterm survivors, concerns about the medium-and long-term consequences of their treatment regimens have led to multiple quality-of-life (qol) studies that have demonstrated significant emotional, cognitive, and physical deterioration after treatment 2,3 . Those studies showed that symptoms such as muscle stiffness, breast sensitivity, tendency to take naps, and difficulty concentrating were common and associated with poor physical functioning and emotional well-being [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Because "chemo-brain" is mainly a subjective phenomenon, it is important to develop techniques to objectively measure neurophysiologic or anatomic changes [223][224][225][226] . Cytokines such as IL-1 and interferons may play a role, according to some animal experiments.…”
Section: Herbsmentioning
confidence: 99%